WHAT MOTIVATES PEOPLE TO PAY ZAKAT, INFAQ, SADAQAH AND WAQF (ZISWAF) THROUGH ONLINE CROWDFUNDING PLATFORMS? (International Journal of Islamic Business, 2024)
Online crowdfunding platforms are web-based platforms designed for fundraising through a collaborative concept. These platforms are claimed to enhance interest in Zakat, Infaq, Sadaqah and Waqf (ZISWAF) contributions due to the convenience they offer. To evaluate this claim, this study aims to examine the influence of literacy, transparency, accountability, religiosity, and trust on the interest in fulfilling ZISWAF obligations through crowdfunding platforms in Indonesia. Employing a quantitative approach, the research involved 182 respondents from the academic community who completed an online questionnaire distributed to 15 universities with ZISWAF institutions on their campuses. The data were analysed using multiple linear regression method. The findings reveal that accountability variable does not significantly influence interest in fulfilling ZISWAF through online crowdfunding platforms in Indonesia. However, literacy, transparency, religiosity, and trust positively and significantly impact this interest. These results provide important insights into the determinants of individual interest in performing ZISWAF. Specifically, online crowdfunding platforms must ensure institutional accountability in ZISWAF fundraising activities. Additionally, platforms should increase transparency by publishing financial and other critical reports to maintain public trust. Therefore, this study contributes to the development of more effective strategies for optimizing online ZISWAF fundraising.